A Analysis of the Marketing System for Tapioca Flour Brands of Dua Ibu Tani Product of PT Haji Muhammad Ilyas Bogor Regency.: Analysis of the Marketing System for Tapioca Flour Brands of Dua Ibu Tani Product of PT Haji Muhammad Ilyas Bogor Regency - Rhamadanty, Fadhila Arnelia; Sulandjari, Kuswarini; Wicaksana, Indrajit (Universitas Pekalongan, 2025)
Sukaraja Sub-district has a lot of cassava land that supports the development of the tapioca flour industry, including PT Haji Muhammad Ilyas as the largest tapioca flour producer in Sukaraja Sub-district. The marketing system of PT Haji Muhammad Ilyas involves many actors, which causes price increases for each actor. This study analyzed the production cost structure, marketing channels, marketing institution functions, marketing margins, farmer's share, and marketing efficiency. Using quantitative and qualitative methods, the study involved 13 respondents using snowball and purposive sampling techniques. The data analysis used was cost structure analysis, marketing margin, marketing efficiency, and farmer's share. The results showed that raw material costs accounted for 86.87% of total production costs, with three main marketing channels involving producers, distributors, retailers, and MSMEs. The marketing margin in marketing channel I is Rp. 440,000, channel II is Rp. 24,000 and channel III is Rp. 20,000. Marketing channel III is the most efficient with an efficiency value of 2.5%, while the farmer's share of channels II and III is considered efficient because it is more than 50%.